2014
DOI: 10.1007/s11419-014-0251-8
|View full text |Cite
|
Sign up to set email alerts
|

Hair analysis for JWH-018, JWH-122, and JWH-210 after passive in vivo exposure to synthetic cannabinoid smoke

Abstract: Hair analysis is often used to confirm abstinence from drug use. However, interpretation of hair analysis results can be challenging, particularly with regard to smoked substances like synthetic cannabinoids, because hair can be contaminated by side-stream smoke. In this study, we measured the concentrations of synthetic cannabinoids in scalp hair after exposure to side-stream smoke from a cigarette containing the synthetic cannabinoids JWH-018, JWH-122, and JWH-210. Three participants exposed their hair to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…There is still limited literature available about the analysis of NPS in hair samples and most methods involve gas chromatography coupled to mass spectrometry (GC‐MS) or (ultra)high performance liquid chromatography((U)HPLC)‐MS(/MS) as detection techniques and are limited to a single analyte or to groups of related substances (i.e., synthetic cannabinoids or cathinones together with phenetylamines or piperazines). Strano‐Rossi et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is still limited literature available about the analysis of NPS in hair samples and most methods involve gas chromatography coupled to mass spectrometry (GC‐MS) or (ultra)high performance liquid chromatography((U)HPLC)‐MS(/MS) as detection techniques and are limited to a single analyte or to groups of related substances (i.e., synthetic cannabinoids or cathinones together with phenetylamines or piperazines). Strano‐Rossi et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, cathinones are unstable under these conditions . Alternative options consist of methanol or ethanol incubation for 3 to 16 h or overnight sonication with aqueous solutions (appropriate for cathinones and phenetylamines only) . Data about the efficiency of the different extraction techniques are unavailable in the literature due to the lack of reference materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hair is analyzed to determine historical drug use in consumers, while tissue samples are analyzed post-mortem and reveal substances consumed prior to death. One of the main challenges that arise when analyzing hair is the interpretation of results; it is essential to ensure true positives by screening for not only parent compounds, but also metabolites, as passive exposure to SCs contained in smoke has been reported to cause false positives [138][139][140]. Studies have also demonstrated that, for certain compounds, smoke condensates contain known metabolites of the parent compound of interest [141].…”
Section: Analysis Of Biological Matricesmentioning
confidence: 99%